Peningkatan Pengetahuan Ibu Hamil tentang Gizi Seimbang di Wilayah Puskesmas Simpang Raya - Widyawati Astuti; Zamli Zamli (Lembaga Pengembangan Kinerja Dosen, 2025)
The nutritional awareness of pregnant women in the Simpang Raya Community Health Center (Puskesmas) in Banggai Regency is still relatively low, necessitating educational efforts to increase their understanding of the importance of balanced nutrition during pregnancy. This community service activity aims to improve the knowledge of pregnant women through participatory and educational nutrition counseling held for one week in the Puskesmas hall. The methods used included interactive lectures, group discussions, and healthy menu preparation simulations, supported by leaflets adapted to the local context. A total of 40 pregnant women from various trimesters of pregnancy participated in the activity and were assessed using pre- and post-test instruments. The results of the activity showed a significant increase in participant knowledge, from 43% in the